Flux lattice melting and dimensional crossover in Bi-2212 single crystals - Kes, P.H.; Pastoriza, H.; Li, T.W.; Cubitt, R.; Forgan, E.M.; Lee, S.L.; Konczykowski, M.; Khaykovich, B.; Majer, D.; Fuchs, D.T.; Zeldov, E. (EDP Sciences, 1996)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Leiden University; Países Bajos